Genotoxic effects of high dose rate X‐ray and low dose rate gamma radiation in Apc(Min/+) mice - Graupner, Anne (Environ Mol Mutagen, 2017)
Risk estimates for radiation‐induced cancer in humans are based on epidemiological data largely drawn from the Japanese atomic bomb survivor studies, which received an acute high dose rate (HDR) ionising radiation. Limited knowledge exists about the effects of chronic low dose rate (LDR) exposure, particularly with respect to the application of the dose and dose rate effectiveness factor. As part of a study to investigate the development of colon cancer following chronic LDR vs. acute HDR radiation, this study presents the results of genotoxic effects in blood of exposed mice. CBAB6 F1 Apc(+/+) (wild type) and Apc(Min/+) mice were chronically exposed to estimated whole body absorbed doses of 1.7 or 3.2 Gy (60)Co‐γ‐rays at a LDR (2.2 mGy h(−1)) or acutely exposed to 2.6 Gy HDR X‐rays (1.3 Gy min(−1)). Genotoxic endpoints assessed in blood included chromosomal damage (flow cytometry based micronuclei (MN) assay), mutation analyses (Pig‐a gene mutation assay), and levels of DNA lesions (Comet assay, single‐strand breaks (ssb), alkali labile sites (als), oxidized DNA bases). Ionising radiation (ca. 3 Gy) induced genotoxic effects dependent on the dose rate. Chromosomal aberrations (MN assay) increased 3‐ and 10‐fold after chronic LDR and acute HDR, respectively. Phenotypic mutation frequencies as well as DNA lesions (ssb/als) were modulated after acute HDR but not after chronic LDR. The Apc(Min/+) genotype did not influence the outcome in any of the investigated endpoints. The results herein will add to the scant data available on genotoxic effects following chronic LDR of ionising radiation. Environ. Mol. Mutagen. 58:560–569, 2017. © 2017 The Authors Environmental and Molecular Mutagenesis published by Wiley Periodicals, Inc. on behalf of Environmental Mutagen Society